The role of ghrelin in the regulation of food intake in patients with obesity and anorexia nervosa - Dostálová, Ivana; Haluzík, Martin (Physiological research, 2009)
Gastrointestinal hormones play an important role in the neuroendocrine regulation of food intake and postprandial satiety. Ghrelin is a 28-amino acid orexigenic peptide produced mainly by the stomach that is involved in both the long-term regulation of body weight and the short-term regulation of postprandial satiety. Impairments in ghrelin secretion may in concert with other factors play an important role in the development of both obesity and anorexia nervosa. Despite an intensive research the critical factors regulating physiological postprandial ghrelin response in healthy individuals and its modification by the presence of obesity and anorexia nervosa are only partially understood. The potential contribution of ghrelin to the differences of diet- vs. surgical-induced weight losses in morbidly obese patients is now also being recognized. The aim of this review is to summarize the current knowledge about the physiology and pathophysiology of ghrelin and to discuss its potential in the prevention and/or treatment of obesity and anorexia nervosa.
Keywords: Ghrelin; přijímání potravy; financování organizované; Obesity; Financing, Organized; Eating; Anorexia Nervosa; lidé; ghrelin; obezita; mentální anorexie; Humans